Government Regulation and Lifecycle Wages: Evidence from Continuing Coverage Mandates - J. Catherine Maclean; Douglas A. Webber (Institute of Labor Economics (IZA), 2019)
We examine the lifecycle wage effects of health insurance market regulation that compels private insurers to offer continuing coverage to beneficiaries. Using a panel of male workers drawn from the National Longitudinal Survey of Youth 1979, we model wages across the lifecycle as a function of the mandated number of months of continuing coverage at labor market entrance. Access to continuing coverage is plausibly valuable to young workers as this benefit facilities job mobility, which is important for early career wage growth and lifecycle wages, but is costly to firms. We show that more generous mandated continuing coverage at labor market entrance causes an initial wage decline of roughly 1% that reverses after five years in the labor market leading to higher wages later in the career. Wage increases are observable up to 30 years after labor market entrance. We provide suggestive evidence that increased job mobility early in the career is a mechanism for the observed wage effects.
Keywords: J3; H2; I13; 330; regulation; job lock; continuing coverage; wage determination; persistence